Relationships between cultural orientations, shared ethical values, job characteristics, and organizational commitment for turkish industrial sales and retail managers - (:unkn) unknown (My University, 1995)
This study examines the relationship between cultural orientations, shared corporate ethical values, job characteristics, and organizational commitment for Turkish industrial sales managers and retail managers, replicating and extending the study done by Hunt, Wood, and Chonko (1989). This comparative study found that organizational commitment is a positive function of both Turkish industrial sales and retail managers’ personal attributes/characteristics, shared corporate ethical values within companies, and task identity, autonomy, variety, and feedback as main components of job characteristics. The perceived level of cultural orientations of managers, on the other hand, differs significantly between two groups: Companies with bureaucratic orientations affect organizational commitment of their employees negatively whereas innovative and supportive ones affect positively. © Taylor & Francis Group, LLC.
Keywords: Ethics; Job characteristics; Organizational commitment; Turkey; Values